Dinamika Komunikasi Organisasi dalam Praktik Teleworking Tim Pengembang Perangkat Lunak - Ajengmas Restia Kumara; Raden Teduh Dirgahayu; Kholid Haryono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The COVID-19 pandemic has been a catalyst in changing work culture. Government regulations in implementing restrictions on social activities to suppress the spread of the COVID-19 virus have become a strong trigger for companies (including software developers) to change their work system from conventional to teleworking. The forced changes that must be made cause the process to be less systematic. One of the challenges as well as an important factor in the success of teleworking is organizational communication. Communication dynamics in teleworking practices that occur in software development teams occur at every development phase. In fact, to obtain quality software quality results, a good development team performance is required. One of the things to achieve this is with good organizational communication as well. Therefore, it is important to know how the dynamics of organizational communication in the software development team as a result of changes in the way of communication at work after the implementation of the teleworking method. This study uses Adaptive Structural Theory, because in this theory communication is placed in an important position in a relationship within the group. The results of testing the hypotheses in this study showed that they were accepted, but some hypotheses did not show significant results. The coefficient of determination on the Decision Result variable is 0.273 indicating that the Decision Result variable is influenced by other variables in this study by 27.3%. Furthermore, the Teleworking Application variable is 0.436 which indicates that the Teleworking Application variable is influenced by other variables in this study by 43.6%. Finally, the Decision Process variable is 0.097 which indicates that the Decision Process variable is influenced by other variables in this study by 9.7%.